Near-critical and supercritical hydrothermal flow synthesis of metal oxide nanoparticles and hybrid metal oxide nanoparticles presenting clickable anchors - Daschner de Tercero, Maren (KIT Scientific Publishing, 2014)
The continuous hydrothermal flow synthesis of functionalized and non-functionalized nanoparticle dispersions was pursued. Besides improving the understanding of the relationship between process variables and the resulting nanoparticle dispersions, the usability of this process was extended by introducing clickable organic modifiers, a step toward the development of a convenient and versatile process for the synthesis of metal oxide nanoparticles with universal anchors on their surface.